2019
DOI: 10.1002/pon.5070
|View full text |Cite
|
Sign up to set email alerts
|

How are caregivers involved in treatment decision making for older people with dementia and a new diagnosis of cancer?

Abstract: Objective To explore how caregivers are involved in making treatment decisions for older people living with dementia and a new diagnosis of cancer. Method A systematic review of PubMed, CINAHL, PsycINFO, Web of Science, and Scopus databases was conducted. Studies recruiting formal or informal caregivers for older people with dementia and a diagnosis of cancer were considered for inclusion. Results Of 1761 articles screened, 36 full texts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Late communication of diagnosis provided minimal opportunity for decision-making advocacy, restorative treatment or preparation for end-of-life. This inhibited rather than promoted best practice and is consistent with recent research (Huang et al 2017;Witham et al 2017;Cook and McCarthy 2018;McWilliams et al 2018;Martin et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Late communication of diagnosis provided minimal opportunity for decision-making advocacy, restorative treatment or preparation for end-of-life. This inhibited rather than promoted best practice and is consistent with recent research (Huang et al 2017;Witham et al 2017;Cook and McCarthy 2018;McWilliams et al 2018;Martin et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…A vital first step in addressing the needs of people with cancer who also have dementia is knowing that someone has dementia. Several studies have, however, found that oncology staff can be unaware when someone has dementia or memory problems (Courtier et al, 2016;McWilliams et al, 2018a;Martin et al, 2019;Ashley et al, 2020;Hopkinson et al, 2020). Documentation of dementia diagnoses in oncology records is inconsistent (Ashley et al, 2020;Courtier et al, 2016) and many oncology assessment forms and staff do not ask about memory problems (Ashley et al, 2020;4-Griffiths et al, 2020;Courtier et al, 2016), possibly because the prevalence of dementia-related memory difficulties and benefits of their identification for patient care are not yet well recognised amongst oncology staff (Courtier et al, 2016).…”
Section: The Challengesmentioning
confidence: 99%
“…This parallel increase in both dependence and cancer in an older population induces ethical debates on how to balance the benefits of specific cancer treatments—evaluated, for example, through quality of life—and their potential harms—linked, for example, to excessive toxicity despite the recent improvement in the adaptation of treatment to the elderly [ 4 ]. It also leads to questions about how to validate treatment decisions in cognitively impaired populations and to collect consent from the patient and his/her family [ 5 , 6 , 7 ]. In this context, the cancer continuum of care may be influenced by organizational, cultural, and ethical barriers associated with the lack of knowledge of the healthcare team, including nurses of nursing homes.…”
Section: Introductionmentioning
confidence: 99%